Infecciones asociadas a la atención en salud en unidades de cuidado intensivo durante la pandemia por COVID 19, una revisión narrativa (2023)
Introduction: Healthcare-associated infections (HAIs) constitute an important public health problem worldwide; they also generate high costs for the healthcare system, affecting the quality of care. During the Covid-19 pandemic, many patients required hospitalization in intensive care units (ICU), showing a progressive increase in HAI reports. Objective: To describe, through a narrative review of the literature, healthcare-associated infections in adult ICUs during the Covid-19 pandemic. Methodology: A narrative review of the literature was carried out following the Whittermore and Knafl five-phase model. Searches were performed by constructing algorithms based on MeSH and DeSC terms linked by Boolean connectors in the Pubmed, ScienceDirect, LILACS and Scielo databases, identifying 3768 studies to which selection filters and eligibility criteria were applied, resulting in 9 studies for analysis. Results: Most were retrospective studies, published between 2020 and 2022. A total of 45539 patients were included, highlighting that male patients over 70 years of age with chronic comorbidities were the most affected by HAIs during their stay in the ICU. Infections were associated with the respiratory tract, urinary tract and bloodstream, with Staphylococcus aureus, Klebsiella pneumoniae and Enterococcus faecalis as the most prevalent etiologic agents. Conclusions: During the Covid-19 pandemic the number of patients requiring ICU increased, the presence of invasive devices for functional support, comorbidities and age represent risk factors for developing HAIs, Staphylococcus aureus, was the bacterium most associated with HAIs. Prevention strategies should be reinforced in ICUs.